Functional Textiles and Clothing - Majumdar, Abhijit; Gupta, Deepti; Gupta, Sanjay (Springer Nature Singapore : Imprint: Springer, 2019)
This volume contains select papers presented during the Functional Textiles and Clothing Conference 2018. The book covers the recent scientific developments, cutting edge technologies, innovations, trends, challenges and opportunities in the field of functional and smart textiles and clothing. The contents of this volume will be of interest to researchers, professional engineers, entrepreneurs, and market stakeholders interested in functional textiles and clothing.